1, 2, 4-trihydroxynaphthalene-2-O-β-D-glucopyranoside: A new powerful antioxidant and inhibitor of Aβ42 aggregation isolated from the leaves of Lawsonia inermis. Issue 10 (19th May 2019) - Dhouafli, Zohra; Ben Jannet, Hichem; Mahjoub, Borhane; Leri, Manuela; Guillard, Jérôme; Saidani Tounsi, Moufida; Stefani, Massimo; Hayouni, El Akrem
Abstract: Mounting evidence indicates free radicals as toxic species causing damage to human cells leading to the pathogenesis of many diseases such as neurodegenerative disease. Plant derived antioxidants are considered as promising strategy to prevent free radical toxicity. In this study, the crude extract (CE), 50%MeOH, Petroleum Ether (PE) and Ethyl acetate (EA) fractions of Lawsonia inermis leaves were investigated for their antioxidant activity and their ability to counteract amyloid-β42 (Aβ42 ) aggregation. Elution of the most bioactive fraction (EA) on silica gel column chromatography led to six sub-fractions. The most active sub-fraction (1) was further resolved on silica gel column chromatography. A new compound with powerful antioxidant and anti-Aβ42 aggregation properties was purified and characterised by spectroscopic methods as 1, 2, 4-trihydroxynaphthalene-2- O -β-D-glucopyranoside (THNG). This finding suggests that the antioxidant and anti-Aβ42 aggregation activities of L. inermis leaves are strongly correlated to this compound. Abstract :